'Mark them with my Mark': Human Branding in Egypt. Issue 1 (June 2022) - Karev, Ella
This paper analyzes the Aramaic and Egyptian textual evidence for the practice of marking enslaved persons in Late Period Egypt, concluding that the terminology of the period refers to branding, not tattooing, as previously suggested. Both branding and tattooing existed as forms of body mutilation, but these practices inhabited different spheres of social power; branding marked one as property, whereas tattooing was religious and decorative. Bearing in mind the use of branding as an indication of ownership, the evidence of tattooing as a cultic (and particularly feminine) practice, and the etymology and usage of the Aramaic terms, this paper proposes that the body mutilation practiced in this period on enslaved persons was branding, not tattooing. The identification of these marks as brands emphasizes the dehumanization of these enslaved persons and implies that their status was on par with other property such as cattle.